Triacylglycerol profile as a chemical fingerprint of mushroom species: evaluation by principal component and linear discriminant analyses. - Barreira, João C.M. (2013)
Mushrooms are becoming relevant foods due to their nutritional, gastronomic and pharmacological properties, namely antioxidant, antitumor and antimicrobial properties. However, despite several mushroom species have been chemically characterized, the evaluation of triacylglycerol (TAG) profile remained nearly discarded. Since TAG was formerly used to assess the authentication of highly valued commercial oils, and the distribution of fatty acids on the glycerol molecule is genetically controlled, the potential of TAG profile to act as taxonomical marker was evaluated in 30 wild mushroom species. Principal component analysis and linear discriminant analysis were used to verify the taxonomical rank (order, family, genus or species) more related with the detected TAG profile. The results pointed out that the ability of TAG profile to discriminate mushroom samples increased for the lower taxonomical ranks, reaching a maximal performance for species discrimination. Since there is high resemblance among mushroom species belonging to the same genus and considering that conservation techniques applied to mushrooms often change their physical properties, this might be considered as a valuable outcome with important practical applications.